2014
DOI: 10.1016/j.jpedsurg.2014.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of RET and NRG1 polymorphisms in Indonesian patients with Hirschsprung disease

Abstract: Background Hirschsprung disease (HSCR) is a neurocristopathy characterized by absence of intramural ganglion cells along variable lengths of the gastrointestinal tract in neonates. Three polymorphisms, rs2435357, within a conserved transcriptional enhancer of RET, and, rs7835688 and rs16879552, within intron 1 of NRG1, have been shown to be associated with isolated forms of HSCR. We wished to replicate these findings, and study the interactions between these variants, in Indonesian HSCR patients. Methods Six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 18 publications
5
37
0
Order By: Relevance
“…Mutation and functional changes of these genes had been indicated, whereas the details of the regulations are still not well known. In recent years, some novel genes have been detected in the segments of HD, such as WNT3A [17], MeCP2 [18], NRG1 [19], etc, but none of these were found to further promote the pathogenesis. Our results showed that autophagy, an evolutionarily process, was involved in HD.…”
Section: Discussionmentioning
confidence: 99%
“…Mutation and functional changes of these genes had been indicated, whereas the details of the regulations are still not well known. In recent years, some novel genes have been detected in the segments of HD, such as WNT3A [17], MeCP2 [18], NRG1 [19], etc, but none of these were found to further promote the pathogenesis. Our results showed that autophagy, an evolutionarily process, was involved in HD.…”
Section: Discussionmentioning
confidence: 99%
“…13 Other examples are NRG1 common variants rs16879552 and rs7835688. These polymorphisms have been related to Hirschsprung disease in Asian ancestry cases [14][15][16] ; however, they are not associated with Hirschsprung disease in white ancestry patients. 17,18 a The gene and variants genotyped, allele frequencies in infants with gastroschisis and controls, the OR, and its 95% CI, with statistical significance values (P values), are shown.…”
Section: Discussionmentioning
confidence: 89%
“…This is important because known genetic causes for HSCR are partially penetrant suggesting gene-gene or gene-environment interactions cause HSCR. This was demonstrated dramatically in mice by the observation that Ret+/− mice never have distal bowel aganglionosis (McCallion et al, 2003), but develop HSCR-like disease more readily than WT when other mutations or non-genetic risk factors are present (Arnold et al, 2009; Carrasquillo et al, 2002; Fu et al, 2010; Gunadi et al, 2014; Lake et al, 2013; McCallion et al, 2003; Phusantisampan et al, 2012; Wallace and Anderson, 2011). In contrast to mice, humans with a single inactive RET allele (i.e., ~30% of HSCR cases) have about a 50% chance of having HSCR (Amiel et al, 2008).…”
Section: Discussionmentioning
confidence: 99%